The Influence of Depth of Plantation to the Growth Rate of Eucheuma cottonii Seaweed Cultivated by Longline Method in Mlonggo Beach, Jepara Regency - Susilowati, Titik; Rejeki, Sri; Zulfitriani, Zulfitriani; Dewi, Eko Nurcahya (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2012)
The aim of the research was to evaluate the influence of three different depth of plantation of Eucheuma cottonii seaweed to the relative and daily growth rate of seaweed.   The experiment   was  designed using a Completely Randomized Design with 3 treatments (25, 50 and 75 cm) depths of Eucheuma  cottonii seaweed. Each treatments was done in triplicate.   Data of the relative and daily growth rate of seaweed are expressed as mean ± standard deviation and then  were analysed using one way Analysis of Variance (ANOVA). A Duncan Multiple test was applied to find out the difference among the treatments. Based on the results, the different depth of plantation gave a highly significant influence (p<0.01) to the the relative and daily growth rate of seaweed. The treatment for 25 cm of the depth plantation showed the relative growth of seaweed of 910% , nearly 3 times of 75cm of depth plantation. The result of this research indicated that the 25 cm depth of plantation was the best relative and daily growth rate of seaweed of all treatments. Key words : The depth of plantation , relative growth rate, daily growth rate, Eucheuma cottoniii